2020
DOI: 10.1101/2020.10.12.20209221
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Presence Of Infection By Mycobacterium Avium Subsp. Paratuberculosis In The Blood Of Patients With Crohn’s Disease And Control Subjects Shown By Multiple Laboratory Culture And Antibody Methods

Abstract: Mycobacterium avium subspecies paratuberculosis (MAP) has long been suspected to be involved in the etiology of Crohns disease (CD). An obligate intracellular pathogen, MAP persists and influences host macrophages. The primary goals of this study were to assess the degree of viable culturable MAP bacteremia in humans, definite identification of the organisms cultured and to assess if CD patients have a significantly higher rate of MAP infection compared to controls. A secondary goal was to compare the effica… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
2
8
0
Order By: Relevance
“…The proposed association implies that evidence of MAP infection may be present in human UvM lesions and patients. Researchers have developed methods of detecting MAP in human tissue (140), blood (141), and feces (142,143). These identification methods can be applied to human UvM patients.…”
Section: Possible Animal Models the Implications To Humans And The Po...mentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed association implies that evidence of MAP infection may be present in human UvM lesions and patients. Researchers have developed methods of detecting MAP in human tissue (140), blood (141), and feces (142,143). These identification methods can be applied to human UvM patients.…”
Section: Possible Animal Models the Implications To Humans And The Po...mentioning
confidence: 99%
“…However, it is important to note again that sun exposure, in contrast to CM, is an unproven risk factor for UvMs presenting in the posterior region of the eye (9,167). Chemical fertilizers, ammonium nitrate, and various military exposures are other plausible agents that may underlie risk and should be considered when interpreting findings (140)(141)(142). The reader is reminded that association does not prove causation.…”
Section: Limitationsmentioning
confidence: 99%
“…Extensive studies have been reported since the publication of these findings that show Map is the causative agent of CD. See references [ 28 , 29 , 30 ] for more detailed information.…”
Section: Original Isolates Of Map From Humans With CD Elicited An Immune Response Similar To the Response Elicited By mentioning
confidence: 99%
“…Recently, a multi-laboratory study employing blind testing of whole blood samples by multiple culture techniques, found widespread viable MAP bacteremia in the 61 CD patients and 140 non-CD control subjects. Nine subjects with a positive Phage assay (4/9) or MAP culture (5/9) were again positive with the Phage assay one year later (Kuenstner et al, 2020). Of the serological methods, the Hsp65 antibody method was best for identifying CD patients from non-CD controls (Kuenstner et al, 2020).…”
Section: Introductionmentioning
confidence: 99%